Catalisadores para a conversão de glicerol a ácido acrílico em um e dois leitos - Bezerra, Franciel Aureliano (2018)
With the growth of biodiesel production, surplus of glycerol has been obtained, which needs to have an application to valorize and make feasible the production of this renewable fuel. In order to obtain an application to glycerol, in this work the process of oxidative dehydration of glycerol was studied. The first part of the work consisted of a thermodynamic study, using the commercial software UniSim. As result, it has been shown that the acrylic acid formation is not thermodynamically favorable, but reactive conditions such as 300 °C and atmospheric pressure and catalysts with medium acidity and oxidative properties may be indicated, which avoid decomposition reactions and successive oxidations of glycerol. In the second part, the oxidative dehydration of glycerol with vanadium and/or molybdenum oxides supported on alumina was studied. The addition of the metal oxides increased the catalytic activity and minimized the deactivation of the catalysts. Furthermore, the activation energy was calculated for the material containing vanadium and molybdenum (Ea = 57.1 kJ mol-1) and this catalyst showed the highest selectivity for acrolein, 75 %, with high space time (W/F = 840 s). Although there was no high selectivity for acrylic acid, it is observed that the material containing molybdenum and vanadium has the most promising performance. Finally, this reaction was studied using tungsten bronze oxides, modified with niobium, vanadium and molybdenum, prepared by the co-precipitation method. The results showed that the insertion of niobium increased the selectivity for acrolein, while the material containing vanadium showed the highest formation for acrylic acid. The reaction was also carried out in a double bed, containing an acid catalyst (W0,8Nb0,2) and an oxidative (W0,8V0,2), with an increase from 18 to 25 % in the selectivity to acrylic acid, in relation to the bed system single. The reaction with the molybdenum bronze (MoVNbTe) in the oxidant bed resulted in 62 % of selectivity for acrylic acid, with low formation for heavy compounds and COx, but the reaction using only the M1 material presents a great formation of COx, resulting from oxidations sequences.